Non-target effects on soil microbial parameters of the synthetic pesticide carbendazim with the biopesticides cantharidin and norcantharidin - Hainan Shao (Nature Portfolio, 2017)
Abstract Considering the fact that biopesticides are increasingly used to replace synthetic pesticides in pest control, it is necessary to assess their ecotoxicity and especially their non-target effects on soil microorganisms, which is largely unknown. In this study, the effects of the synthetic pesticide carbendazim and the biopesticides (cantharidin and norcantharidin) on soil microbial parameters in a silt loam soil were evaluated. By using commercial formulations at the recommended and higher rates, both cantharidin and norcantharidin induced adverse effects on soil invertase, phosphatase activities and fungal gene structure, but these changes were transient. After about two weeks, the harmful effects owing to the application of pesticides phased out and eventually became comparable with non-treated samples. The degradation of cantharidin and norcantharidin was rapid and can be completed within a few days in the soil. None of the three pesticides caused significant shifts in urease activity. This study provides a comprehensive assessment of the soil microbial toxicity of these biopesticides for reasonable and efficient usage.